Acetabular Fracture Outcomes and Complications: An International Comparison - Dallman, Johnathan; Ayres, Jack; Nolte, Jack; Everist, Brian; Crist, Jamie; Frager, Luke; Sojka, John; Malancea, Radu; Heddings, Archie (Kansas Journal of Medicine, 2024)
Introduction While there have been many technological advances in the treatment of acetabular fractures since the landmark article by Judet and Letournel, the effectiveness of many of these advances have not been definitively determined. Comparing patient outcomes between two countries with differing amounts of technological resources may identify the efficacy of such resources. Methods This study retrospectively compared 489 patients (373 US, 116 Romania) who underwent open reduction and internal fixation (ORIF) for acetabular fracture(s) in a Romanian trauma center and a United States (US) trauma center between February 2011 and August 2018. Results US patients had a higher rate for the following comorbidities: diabetes (p=.0268), obesity (p<.0001), and hypertension (p<.0001). US patients had a significantly shorter pre-op delay (p<.0001). Matta’s criteria for initial quality of reduction did not vary significantly between countries (p=.1101). No significant difference was found in rates of DVT (p=.0722), postoperative infections (p=.2819), sciatic nerve lesions (p=.9999), or loss of reduction (p=.9999). US patients had significantly higher Brooker criteria scores for heterotopic ossification (p<.0001). Conclusions There were no significant differences in outcomes between US and Romanian patients even though US patients received treatment using the latest technology while Romanian patients were treated using substantially fewer resources. Given that technological advances in surgical technique come at a considerable price, it makes sense to build upon this study to gain a more precise understanding of how these advances improve outcomes for patients, and whether or not they are worth the added cost.